Oxidative Stress in the Pathogenesis of Neurodegenerative Diseases - Maria-Carolina Jurcau; Anamaria Jurcau; Razvan-Gabriel Diaconu (Stresses)
Neurodegenerative diseases are devastating conditions with a rising incidence and prevalence due to the aging of the population for which we currently do not have efficient therapies. Despite compelling evidence provided by basic research on the involvement of oxidative stress in their pathogenesis, most trials with antioxidants have failed. The reasons may relate to the low bioavailability of the used compounds or to starting therapy late, when the pathogenic cascades have already induced irreversible damage. The current review discusses the sources of oxidative stress in the central nervous system, the involvement of reactive oxygen species in the pathogenesis of Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis, and the importance of further research on improved delivery methods of antioxidants as well as the search for biomarkers that could help in early diagnosis in the hope of finding more efficient therapies for these diseases.